Interpretation of the character of Ahmad Farghani in the drama (The Peerian Journal, 2023)
This article analyzes the dramatic work of the character of Ahmad Farghani. The drama "Ahmed Farghani" by Ibrahim Rahim was analyzed. The object of research is a historical figure, that is, Ahmad Farghani. In the article, the ideas put forward through the artistic image of Ahmad Farghani were revealed